(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
In this present study, three (3) new sunshine based models were developed and evaluated using observed monthly average daily global solar radiation and sunshine hours meteorological variables spanning through thirty one years (1980-2010). The estimated global solar radiation values obtained from the empirical regression models for the developed models and nine (9) distinctive existing sunshine based models were compared through validation indicators of Mean Bias Error (MBE), Root Mean Square Error (RMSE), Mean Percentage Error (MPE), t – test, Nash – Sutcliffe Equation (NSE), Index of Agreement (IA) and coefficient of determination (R2) allowing the identification and recommendation of the most accurate model suitable for the estimation of global solar radiation in Kano and Ikeja located in the Sahelian and Coastal regions respectively. The results in this present study revealed that the developed exponent exponential and quadratic latitude 2 sunshine based models were found more appropriate for estimation of global solar radiation in Kano (Latitude 12.05 and Longitude 8.20 ) and Ikeja (Latitude 6.58 and Longitude 3.33 ) respectively. The evaluated existing linear (1st order) and quadratic (2nd order) sunshine based models for Kano were found more suitable for the estimation of global solar radiation as compared with those found through literature survey. The empirical regression equations and the values of the validation indicators obtained in this study for each model varies significantly in each of the regions under investigation indicating that the twelve (12) sunshine based models are site – specific. The correlation between the